"Candidatus Phytoplasma solani" associated with Eucalyptus witches' broom in Iran. Issue 1 (14th October 2017) - Baghaee‐Ravari, S.; Jamshidi, E.; Falahati‐Rastegar, M.
Summary: During summer of 2015, Eucalyptus camaldulensis plants showing witches' broom, little leaf and general yellowing of the foliage were observed in west of Fars and Khozestan province of Iran. DNA from samples of 22 symptomatic and two asymptomatic trees was extracted and subjected to molecular analyses. Nested‐PCR test using R16F2n/R16R2 primers confirmed phytoplasma presence in 63% of symptomatic Eucalyptus plants. Sequence analysis along with virtual RFLP of the 16S ribosomal DNA allowed to classify three Eucalyptus witches' broom strains into the "stolbur" (" Candidatus phytoplasma solani") 16SrXII‐A subgroup. Comparison of the sec A and sec Y gene sequences with sequences deposited in GenBank confirmed the phytoplasma identity. Real and virtual RFLPs of the amplified sec Y gene using Hae III, Mse I and Rsa I restriction enzymes showed profiles indistinguishable from each other. This is the first study reporting E. camaldulensis as a new host species for " Ca . P. solani."